Value relevance of alternative methods of accounting for actuarial gains and losses - Morais, Ana (2008)
The adoption of IAS 19: Employee benefits (2004) provided managers with an important accounting choice affecting the time and placement of actuarial gains and losses recognition. IAS 19 enables a choice between three major accounting methods related to the recognition of actuarial gains and losses of defined benefit plans: profit or loss method, equity recognition method and corridor method. The objective of this paper is to compare the ability of the three alternative methods for recognising actuarial gains and losses to reflect companies’ value. We manually collect information about the accounting method of recognising actuarial gains and losses adopted by 91 European companies listed in EURONEXT100, in 2005, 2006 and 2007. We applied regression analysis to investigate the value relevance of financial information under equity recognition method, profit or loss method and corridor method. Findings suggest that the recognition of all actuarial gains and losses in equity best reflects the market’s valuation of actuarial gains and losses.